Viral hepatitis c and pregnancy - M A Belopolskaya (RUDN Journal of Medicine, 2011)
Based on the literature and our research about effect of pregnancy on HCV, effect of HCV on the course of pregnancy and vertical transmission of HCV recommendations for treatment of pregnant women with HCV are given.